(untitled) (LACCEI, 2024)
The investment made by countries in Research and Development (RD) is part of the government policy that translates into subsidies and loans for professional training and that clearly influences the enrollment process in universities of Central and South America, which have proposals that are oriented towards desirable aspirations for the enrollment of students who contribute to the socioeconomic development of the countries and become a qualified labor force. The originality of the work lies in answering the question of how the Investment in RD, Enrollment in universities determine the labor force in Central and South America and its influence on per capita income? For this, a sample of these indicators of the 17 continental countries was taken, obtained from the World Bank database, processing them in the Excel and Stata software. The results show that there is a direct relationship between investment in RD spending, enrollment in universities and confirms its influence on the creation of the active labor force